2021
DOI: 10.3389/fimmu.2021.721453
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 and CCR9+α4β7– Th17 Cells Promote Salivary Gland Inflammation, Dysfunction, and Cell Death in Sjögren’s Syndrome

Abstract: Previous studies have evaluated the roles of T and B cells in the pathogenesis of Sjögren’s syndrome (SS); however, their relationships with age-dependent and metabolic abnormalities remain unclear. We examined the impacts of changes associated with aging or metabolic abnormalities on populations of T and B cells and SS disease severity. We detected increased populations of IL-17-producing T and B cells, which regulate inflammation, in the salivary glands of NOD/ShiLtJ mice. Inflammation-induced human submandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…However, one study found no such difference ( 11 ). The increased Th17 cell frequency was also noted in the peripheral blood, spleen, and salivary glands of NOD mice ( 29 ).…”
Section: Role Of Cd4 + T Cells In Ssmentioning
confidence: 89%
“…However, one study found no such difference ( 11 ). The increased Th17 cell frequency was also noted in the peripheral blood, spleen, and salivary glands of NOD mice ( 29 ).…”
Section: Role Of Cd4 + T Cells In Ssmentioning
confidence: 89%
“…[45][46][47] Indeed, IL-17 has been shown to impair salivary gland function by affecting calcium movement. [48] It has been linked to promoting salivary gland inflammation and cell death in conditions like SS, [49] which can activate nuclear factor κB. This transcription factor plays a leading role in regulating the expression of various proinflammatory cytokines (TNF-α, IL-1β, IL-6, and C-C motif chemokine ligand 2).…”
Section: Discussionmentioning
confidence: 99%
“…It was subsequently found that the aberrant expression of IL-17 induced by metabolic abnormalities contributed to cell lesions and inhibition of tissue recovery in the salivary glands of patients with SS. Furthermore, retinoic A deficiency can exacerbate the imbalance in the Th17/Treg ratio in patients with SS ( 69 ).…”
Section: Pathogenesismentioning
confidence: 99%